Temporal macrodynamics and microdynamics of the postoperative impedance at the tissue–electrode interface in deep brain stimulation patients. Issue 7 (11th November 2013) - Lungu, C; Malone, P; Wu, T; Ghosh, P; McElroy, B; Zaghloul, K; Patterson, T; Hallett, M; Levine, Z
Abstract : Objective: To study the temporal dynamics of tissue impedance after deep brain stimulation (DBS). Background: DBS therapy commonly employs a constant voltage approach, and current delivery to the tissue is a function of electrode–tissue impedance. It is presumed that impedance fluctuates early postimplantation, with implications for variations in current delivery and therapeutic efficacy. We hypothesised that the largest variation will be recorded early after surgery, followed by stabilisation. Methods: Review of impedance checks of implanted DBS systems at standard parameters during the first five months postimplantation. All measurement time points were binned into 1-week periods, and we used repeated measures analysis of variance with Tukey pairwise multiple comparisons correction. The analysis was repeated after normalising impedance values for each subject to that patient's baseline value. Results: There was an initial (non-significant) drop in impedance at week 1, followed by significant increase at week 3 (p=0.0002). There were no further significant differences in impedance values at subsequent time points. Analysis of normalised data showed a significant difference between the initial measurement in postoperative week 1 (normalised value 1) and week 3 (normalised value 1.73, p<0.0001), with no further difference among the subsequent weekly points during the 5-month follow-up. No significant hourly variations were found at any time points. Conclusions: We found major changes in impedance within the first month postimplantation, with no further variation. This is an important confirmation in patients of this temporal dynamics of the impedance of implanted DBS hardware, with potential therapeutic implications.